Development of Teaching Materials using Ai-Based Teachy App at Pela Elementary School - Rahayu, Sri; Hakim, Arif Rahman; Fitrianingsih , Nur (FKIP - Universitas Riau, 2025)
The transformation of education in the digital era requires innovations in developing adaptive and contextual teaching materials. One potential solution is the utilization of artificial intelligence (AI) technology through the Teachy App, an application that assists teachers in automatically designing instructional materials. This study aims to develop AI-based teaching materials using the Teachy App at SDN Pela and to examine their validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, and learning achievement tests. Validation was carried out by subject matter and media experts, while limited and broader trials were conducted on fifth-grade students. The validation results showed an average score of 87.1% (highly valid). Practicality was categorized as very practical with a score of 85%, supported by students' positive responses to the media's design and ease of use. Effectiveness was demonstrated by an increase in the average score from 67.4 (pretest) to 84.7 (posttest), indicating a 17.3-point improvement. Therefore, the findings confirm that AI-based teaching materials developed using the Teachy App are feasible, valid, practical, and effective in supporting elementary school learning.